Impact of Digital Marketing Content on Brand Awareness among Jordanian Consumers - Al-Assaf, Khaled Tawfiq (Journal of Ecohumanism, 2024)
The study aimed to identify the impact of digital marketing content on consumer awareness of the brand. To achieve its objectives, the researcher adopted a descriptive-analytical approach. A data collection tool was developed in the form of a questionnaire consisting of 27 items, which was distributed electronically to a simple random sample of 650 consumers from the study population. A total of 365 valid questionnaires were collected and approved for analysis. Statistical methods appropriate to the study were applied using SPSS 22 for data analysis.The study yielded several key findings, most notably that digital marketing content—specifically information recombination, accessibility, and speed—has a statistically significant effect on Jordanian consumers’ brand awareness at a significance level of (α < 0.05). Notably, accessibility accounted for 35.6% of the variance in consumer brand awareness.Based on these findings, the study recommends that businesses focus on ensuring the accessibility of their digital marketing content to enhance brand awareness among customers. Since the results suggest a deficiency in this dimension, the study also advises companies that provide digital marketing content with information recombination to focus on delivering valuable information to boost positive brand perception among consumers. Additionally, it is essential for businesses to explore effective methods for managing the speed aspect of digital marketing content to positively impact brand recognition, particularly in terms of how relevant advertising content is presented.